THE IMPORTANCE OF TRAINING AND ITS IMPACTS ON ABSENTEEISM TURNOVER IN COMPANIES - Duarte, Dealison Felipe; Caparroz, Priscila Giorlano; Rodrigues, Lilian Segnini (Revista Interface Tecnológica, 2023)
This research aims to analyze the importance of training within companies and its direct relationship with absenteeism and turnover. Lack of training is a common problem in many companies, which do not understand the benefits that a well-trained team can provide. In addition, the lack of training leads to other problems, such as absenteeism and turnover. Based on these problems, a case study was carried out in a company in the Bookstore/Stationery business, located in the city of São Carlos. To this company, the authors give the code name Alpha Company. One of the main purposes of this work is to analyze whether all the theory that was presented in the theoretical discussion is relevant and correlatively corresponding in the corporate world. For this case study, a questionnaire was applied to Alpha Company employees, who could answer anonymously. It is concluded that the lack of training is potentially capable of generating problems, especially absenteeism and staff turnover, and a proposed is presented that can be effective in mitigating these problems and can be used by any company that has the necessary same problems as the research company, in addition to contributing to university-company cooperation.
Keywords: Training; Absenteeism; Turnover